2014
DOI: 10.1016/j.anr.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Evidence-based Postoperative Pain Guidelines via Web for Patients undergoing Abdominal Surgery in South Korea

Abstract: Evidence-based pain guidelines were effective in reducing the pain level of patients as well as improving nurses' knowledge of pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Eight studies reported the numbers of nurses participating, with a mean of 87 (range: 18 to 187). The percentage of nurses approached who agreed to take part was 80-100% in five papers, (Abdalrahim et al, 2011;Innis et al, 2004;Morrisson et al, 2006;Ravaud et al 2003;Zhang et al, 2008), 60-79% in two (Hansson et al, 2006;Hong & Lee, 2014), and not reported in the remaining five papers.…”
Section: Methodological Quality Assessmentmentioning
confidence: 98%
See 4 more Smart Citations
“…Eight studies reported the numbers of nurses participating, with a mean of 87 (range: 18 to 187). The percentage of nurses approached who agreed to take part was 80-100% in five papers, (Abdalrahim et al, 2011;Innis et al, 2004;Morrisson et al, 2006;Ravaud et al 2003;Zhang et al, 2008), 60-79% in two (Hansson et al, 2006;Hong & Lee, 2014), and not reported in the remaining five papers.…”
Section: Methodological Quality Assessmentmentioning
confidence: 98%
“…Two scored 'weak' for selection bias, using convenience sampling with no indication of refusal rate (Lin, Chiang, Chiang & Chen, 2008;Michaels et al, 2007), One study scored 'weak' on blinding, as outcome assessors and participants were aware of the study question (Hong & Lee, 2004). The fourth study had important confounding differences in gender and type of surgery between control and intervention staff groups (Ravaud et al, 2004).…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations